An Overview of Resilience and Academic Achievement of Adolescents in Nigeria - Anakwe, Augustina Izadi; Dikko, Suleiman (NIU Journal of Humanities, 2018)
This paper looks at resilience and academic achievement of adolescents in Nigeria, The paper discusses the concept of resilience, which is a kind of bounce back from risks or traumatic situations, and academic achievement defined as academic success. The work is situated on Richardson Glenn's Three Waves Meta Theory of Resiliency. The first wave discusses the identification of resiliency characteristics. The second wave centres on the processes needed to acquire the characteristics while the third wave discusses the enactment of the processes to explore the characteristics. This work also looks at the risks factors that make students give up easily such as religious crises, terrorism and socio- economic background of the family. The paper also looks at how resilience could be fostered through two main protective factors, the internal and the external factors. The internal factors focus on the individual's assets within him- self-efficacy and locus of control. The external factors are environmental factors which include the family, the school and the community. Based on the issues raised in this paper, recommendations are made.